2023
DOI: 10.3389/fonc.2023.1069467
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between germline genetic findings and abnormal tumor immunohistochemistry staining of mismatch repair proteins in individuals with suspected Lynch syndrome

Abstract: Background and AimsTumor immunohistochemical staining (IHC) of DNA mismatch repair (MMR) proteins is often used to guide germline genetic testing and variant classification for patients with suspected Lynch syndrome. This analysis examined the spectrum of germline findings in a cohort of individuals showing abnormal tumor IHC.MethodsWe assessed individuals with reported abnormal IHC findings and referred for testing with a six-gene syndrome-specific panel (n=703). Pathogenic variants (PVs) and variants of unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Remarkably, one‐third of tumor samples from the PMS2 c.1831dup PV carriers as well as 17% of those from the PMS2 control group displayed an uncommon IHC pattern. Atypical MMR protein expression patterns have recently been reported in 15.2% of samples from patients with suspected LS (Pan et al., 2023). Another study evaluating patients with PMS2 PVs identified a discordant IHC profile in 6% of their tumor samples after excluding samples with isolated PMS2 loss (van der Klift et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, one‐third of tumor samples from the PMS2 c.1831dup PV carriers as well as 17% of those from the PMS2 control group displayed an uncommon IHC pattern. Atypical MMR protein expression patterns have recently been reported in 15.2% of samples from patients with suspected LS (Pan et al., 2023). Another study evaluating patients with PMS2 PVs identified a discordant IHC profile in 6% of their tumor samples after excluding samples with isolated PMS2 loss (van der Klift et al., 2016).…”
Section: Discussionmentioning
confidence: 99%